Evaluación de los Efectos del Acompañamiento Familiar Durante el Parto Humanizado de Gestantes que Acuden al Hospital Alfredo Noboa Montenegro en el Periodo enero - abril 2024. - Merchán Monserrate, Allyson Nayely (2024)
In Ecuador, a few years ago the ESAMYN standards were implemented, which seek to reduce maternal and neonatal death. One of its components is family support, which during the birth process will help reduce stress and anxiety. helping the pregnant woman to better channel the pain, making childbirth easier. The objective of this study is to evaluate the effects of family support during humanized childbirth on the quality of obstetric care provided to pregnant women who attend the Alfredo Noboa Montenegro Hospital. A quantitative methodological approach was used, since the data obtained was through the statistical review of medical records of the pregnant women who were seen in those limited months of January - April 2024, the sample taken was 138 pregnant women who gave birth. delivery in the established months, corresponding to 100% of the population. Once the research instrument was applied, it was found that family support is positively effective in the process of both labor and delivery in patients, providing them with security and support and allowing this procedure to be more satisfactory.